Tofacitinib attenuates arthritis manifestations and reduces the pathogenic CD4 T cells in adjuvant arthritis rats - Gertel, Smadar (Clinical immunology (Orlando, Fla.), 2017)
Copyright © 2017. Published by Elsevier Inc.